Mucinous Cystic Neoplasm in Heterotopic Pancreas Presenting as Colonic Polyp - Abraham, Joji; Agrawal, Vinita; Behari, Anu (JOP. Journal of the Pancreas, 2013)
Context Pancreatic heterotopia in itself is rare in the colon and to the best of our knowledge a neoplasm arising in a heterotopic tissue in the colon has not been reported. We herein report a pancreatic cystic neoplasm arising from heterotopic pancreatic tissue in colon. Case report A 44-year-old lady presented with a history of lower abdominal colic, associated with mucoid loose stools 10-15 times/day. Fecal occult blood was positive on two occasions. On examination, a vague mass was palpable in the left upper quadrant of abdomen. Colonoscopy showed a polypoid growth at the splenic flexure of colon, which on biopsy was reported to be an inflammatory polyp. She underwent a laparoscopic converted to open left hemicolectomy. Post-operatively she developed a intra-abdominal collection which formed a controlled pancreatic fistula after percutaneous drainage. Histopathology revealed pancreatic heterotopia with pancreatic mucinous cystic neoplasm. Conclusion Despite advances in patient care, preoperative diagnosis of heterotopic pancreas is difficult. Image: Pedunculated polypoidal mass.